2020
DOI: 10.1016/j.kint.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The acute kidney injury to chronic kidney disease transition in a mouse model of acute cardiorenal syndrome emphasizes the role of inflammation

Abstract: Acute cardiorenal syndrome is a common complication of acute cardiovascular disease. Studies of acute kidney injury (AKI) to chronic kidney disease (CKD) transition, including patients suffering acute cardiovascular disease, report high rates of CKD development. Therefore, acute cardiorenal syndrome associates with CKD, but no study has established causation. To define this we used a murine cardiac arrest (CA) and cardiopulmonary resuscitation (CPR) model or sham procedure on male mice. CA was induced with pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Leslie S. Gewin 1,2,3 A protective role for sirtuin 6 (Sirt6) in the context of chronic renal injury is reported by Cai et al in this issue of Kidney International. The mechanism is thought to be mediated by Sirt6's deacetylase activity, specifically on b-catenin target genes.…”
Section: Sirtuin 6 and Renal Injurymentioning
confidence: 92%
See 2 more Smart Citations
“…Leslie S. Gewin 1,2,3 A protective role for sirtuin 6 (Sirt6) in the context of chronic renal injury is reported by Cai et al in this issue of Kidney International. The mechanism is thought to be mediated by Sirt6's deacetylase activity, specifically on b-catenin target genes.…”
Section: Sirtuin 6 and Renal Injurymentioning
confidence: 92%
“…Sirt1 can ameliorate acute kidney injury and diabetic kidney disease and reduce fibrosis in the unilateral ureteral obstruction model. 1,2 The mechanisms by which Sirt1 is protective in CKD models include reduction of cyclooxygenase-2 and inhibition of oxidative stress, and targeting of transforming growth factor-beta (TGF-b) signaling, signal transducer and…”
Section: Sirtuin 6 and Renal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The technique described in this paper would be easily modified to allow for prolonged arrest time to study neurologic insult. Mouse SCA models have been utilized to as a clinically-relevant model of both acute kidney injury 31,32 (one day after arrest) and chronic kidney disease (seven weeks after arrest, attributed to prolonged inflammation after reperfusion) 32 . We show that our model of SCA similarly develops markers of AKI, as evidenced by elevated serum creatinine, BUN, and tubular damage 1 day after arrest (Figure 3).…”
Section: Sca Mice Have Evidence Of Prolonged Ischemia After Sca and Kmentioning
confidence: 99%
“…AKI induced by I/R has a complex pathogenesis involving innate and adaptive immune responses [10]. Studies have shown that AKI autophagy induced by I/R plays an important role in AKI in vivo and in vitro [11,12].…”
Section: Introductionmentioning
confidence: 99%